Antifungal activity of the clove essential oil from Syzygium aromaticum on Candida, Aspergillus and dermatophyte species - Pinto, Eugénia; Vale-Silva, Luís; Cavaleiro, Carlos; Salgueiro, Lígia (Journal of medical microbiology, 2009)
The composition and antifungal activity of clove essential oil (EO), obtained from Syzygium aromaticum, were studied. Clove oil was obtained commercially and analysed by GC and GC-MS. The EO analysed showed a high content of eugenol (85.3 %). MICs, determined according to Clinical and Laboratory Standards Institute protocols, and minimum fungicidal concentration were used to evaluate the antifungal activity of the clove oil and its main component, eugenol, against Candida, Aspergillus and dermatophyte clinical and American Type Culture Collection strains. The EO and eugenol showed inhibitory activity against all the tested strains. To clarify its mechanism of action on yeasts and filamentous fungi, flow cytometric and inhibition of ergosterol synthesis studies were performed. Propidium iodide rapidly penetrated the majority of the yeast cells when the cells were treated with concentrations just over the MICs, meaning that the fungicidal effect resulted from an extensive lesion of the cell membrane. Clove oil and eugenol also caused a considerable reduction in the quantity of ergosterol, a specific fungal cell membrane component. Germ tube formation by Candida albicans was completely or almost completely inhibited by oil and eugenol concentrations below the MIC values. The present study indicates that clove oil and eugenol have considerable antifungal activity against clinically relevant fungi, including fluconazole-resistant strains, deserving further investigation for clinical application in the treatment of fungal infections.